PENAMBAHAN DAUN BAYAM MERAH TERHADAP SIFAT ORGANOLEPTIK DAN NILAI GIZI SOSIS IKAN CAKALANG GUNA MENCEGAH ANEMIA PADA REMAJA - Tan, Maria Suryaningsih; Saleh, Asmulyati S (Poltekkes Kemenkes Kupang, 2025)
Parenting is a pattern Anemia is a condition where the hemoglobin level in the body is less than normal. In general, adolescent girls are susceptible to anemia due to inadequate nutritional intake, physical activity and menstruation. Normal Hb levels in adolescent girls are >12 g/dL. Adolescent girls need more iron than adolescent boys, because adolescent girls experience menstruation every month, adolescent girls who experience menstruation for a long period of time will cause anemia. One way to prevent anemia is by providing functional food ingredients that have been developed, namely adding red spinach leaves to skipjack fish sausages, where red spinach has a high iron content which can overcome anemia in young women. The research objective: to determine the organoleptic tests and nutritional content of fish sausages with the addition of red spinach leaves. Research Method: The research used a completely random method (RAL). With the addition of red spinach leaves, there were 4 treatments where P1 10% P2 15% and P3 20% Results: The results of the study showed that the comparison of skipjack tuna meat with the addition of red spinach leaves had an effect on descriptive and hedronic sensory assessments of color and taste attributes. Conclusion: The best organoleptic test results and the panelists liked the most was P2 with the addition of 52 grams of red spinach leaves = 15%. From the research results the author recommends P3: 20% because it has the highest nutritional content. Values ​​in nutritional analysis per slice of 41 pieces: energy 22.27 kcal, protein 1.96 grams, fat 0.26 grams, carbohydrates 2.98 grams, iron 0 .51 mg.